Seleção e utilização de fungos filamentosos livres e imobilizados para remoção de metais pesados - Maristella Ayala Dias Saldanha (2003)
The major goal of this work was to isolate and characterize yeast and filamentous fungus able to remove heavy metal particles from the steel industries water residues. Those microorganism were recovered from water treatment reservoirs and residual water generated during steel production. The fungi recovered from those sites were assayed for growth on increasing concentration, ranging from 5 to 100 mg/l, of chrome, nickel or iron. 15 isolates were selected and re-assayed on a mineral or liquid medium Sabouraud media supplemented with the challenging metal and no differences were observed between either medium. Therefore, Sabouraud liquid medium was selected as the media of choice for further assays and growth conditions standardized to pH ranging from 4.0 to 6.0 ay 35°c. The amount of 100 mg of fungal mass retrieved from Sabouraud media was utilized as initial inoculum in all experiments. The liquid fraction of the incubated material was filtered through a 45 um Millipore membrane and the supernatant analyzed on mass spectrometer for heavy metal measurements. The adsorption capacity was estimated though the equation q = Cf – Ci x biomass (g), where q stands for adsorption capacity and Cf and Ci for final and initial concentration respectively. From the 15 initially selected isolates, ° filamentous fungus and 1 yeast isolate with the highest q values were chosen. They are then tested again against the heavy metals at concentrations ranging from ° to 200 mg/l, and 4 with the better scores were considered for further applications. They were characterized as Aspergillus terreus UFMG-F01 and UFMG-02, Aspergillus niger UFMG-F03 e Phoma sp UFMG-F04. The isolate UFMG-F01 was able to adsorb 78 mg/g of chrome, 77 mg/g of nickel and 100 mg/g of iron. While the isolate UFMG-F02 adsorbed 101 mg mg/l, 42.2 mg/l and 59.9 mg/l of chrome, nickel and iron respectively The isolate UFMG-F03 was able to adsorb 88 mg/l of chrome, 45.5 mg/l of nickel and 30 mg/l of iron, while the isolate UFMG-F04 adsorbed 98 mg/l, , 78 mg/l and 52.2 mg/l of chrome, nickel and iron respectively. The adsorption values observed with A. terreus UFMG-F01 were higher than the usually described for other fungus on the literature. Viable and dead biomass of UFMG-F01 were immobilized on polyurethane, alginate and alumina and challenged with synthetic heavy metal solution as well as steel industry water waste. Polyurethane was, among the materials tested, the one with higher capability of holding fungal biomass at a porosity of 43 / cm. Alginate, for other hand, had poor mechanical resistance and low capacity of synthetic medium. Only dead material was incorporated on alumina and it was able to remove chrome and iron from both waste water and synthetic media. A. terreus showed potential for further use as a bio adsorbent in the steel industry and its comertial application should be perused.